Sadomasochism in everyday life : the dynamics of power and powerlessness - Chancer, Lynn S. (New Brunswick, NJ : Rutgers University Press, 1992)
Lynn Chancer advances the provocative thesis that sadomasochism is far more prevalent in contemporary societies like the United States than we realize. According to Chancer, sexual sadomasochism is only the best-known manifestation of what is actually a much more broadly based social phenomenon. Moving from personal relationships to school, the workplace, and other interactions, Chancer uses a variety of examples that are linked by a recurrent pattern of behavior. She goes beyond the predominantly individualistic and psychological explanations generally associated with sadomasochism (including those popularized in the "how to" literature of the recent Women Who Love Too Much genre) toward a more sociological interpretation. Chancer suggests that the structure of societies organized along male-dominated and capitalistic lines reflects and perpetuates a sadomasochistic social psychology, creating a culture steeped in everyday experiences of dominance and subordination.

In the first part of the book, Chancer discusses the prevalence of sadomasochistic cultural imagery in contemporary America and examines sadomasochism through several perspectives. She develops a set of definitional traits both through existential analysis of an instance of S/M sex and by incorporating a number of Hegelian and psychoanalytic concepts. In the second part of the book, she places sadomasochism in a broader context by exploring whether and how it appears in the workplace and how it relates to gender and race.
Part two: Sadomasochism in its social settings : Employing chains of command: sadomasochism and the workplace -- Engendering sadomasochism: dominance, subordination, and the contaminated world of patriarchy -- Creating enemies in everyday life: following the example of others -- A theoretical finale
Str. [223]-230: Bibliografija
Kazalo
Keywords: struktura društva; moć (društvene znanosti); društveni odnosi; sadomazohizam -- SAD